PENGEMBALIAN ASET NEGARA TERHADAP TINDAK PIDANA KORUPSI MELALUI KERJASAMA INTERNASIONAL BERDASARKAN UNDANG – UNDANG NOMOR 7 TAHUN 2006 TENTANG PENGESAHAN UNITED NATlONS CONVENTION AGAINST CORRUPTION (UNCAC) - ANDI SAPUTRA; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The act of corruption is a violation of the social rights and economic rights of the people, so that the criminal act of corruption can not be classified as ordinary crimes but has become extra-ordinary crimes, so in an effort to enforce it can no longer be done